Disparities in Postoperative Therapy for Salivary Gland Adenoid Cystic Carcinomas. (8th September 2018) - Cassidy, Richard J.; Switchenko, Jeffrey M.; El‐Deiry, Mark W.; Belcher, Ryan H.; Zhong, Jim; Steuer, Conor E.; Saba, Nabil F.; McDonald, Mark W.; Yu, David S.; Gillespie, Theresa W.; Beitler, Jonathan J.
Abstract : Objectives: The patterns of care for salivary gland adenoid cystic carcinomas (ACC) are unknown. We sought to assess predictors of receiving postoperative radiation and/or chemotherapy for patients with nonmetastatic, definitively resected ACC, as well as report unexpected nodal disease. Methods: The National Cancer Data Base was queried for definitively resected nonmetastatic ACC from 2004 to 2014. Logistic regression, Kaplan‐Meier, and Cox proportional‐hazard models were utilized. Propensity‐score matched analysis was employed to reduce confounding variables. Results: A total of 3, 136 patients met entry criteria: 2, 252 (71.8%) received postoperative radiation, with 223 (7.4%) also receiving concurrent chemotherapy. Median follow‐up was 4.87 years. In clinically lymph node negative (cN0) patients, 7.4% had pathologically positive lymph nodes (pN) + after elective neck dissection. Patients who lived closer to their treatment facility and had positive margins were more likely to receive postoperative radiation. Black patients and uninsured patients were less likely to receive radiation. Older age, male sex, advancing stage, and positive surgical margins were associated with worse overall survival (OS). With limited follow‐up, receipt of radiation or chemotherapy was not associated with OS. Conclusion: Postoperative radiation was frequently given for resected ACC, with a minority receiving chemotherapy. Black patients and uninsured patients were less likely to receive radiation. Postoperative radiation and/or chemotherapy had no association with OS but were given in greater frequency in more advanced disease, and our series is limited by short follow‐up. The disparity findings for this rare disease need to be addressed in future studies. Level of Evidence: 2c Laryngoscope, 129:377–386, 2019